Studies on Combining Ability and Heterosis for Seed Yield and Yield Components in Blackgram (Vigna mungo L. Hepper) - Rukminidevi, K.; Bharath, T.; Nagaswathi, K.; Supriya, B. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during kharif (June–September, 2022) and rabi (October–December, 2022–23) at Agriculture Research Station, Madhira, Telangana, India to study on the combining ability analysis in blackgram for yield and its component traits through Line×Tester design. Twenty four crosses derived after crossing six lines and four testers were evaluated in line×tester analysis. Predominance of non-additive gene action was observed for most of the yield components except harvest index, which was under the control of additive gene action. Among the lines TU-94-2, MBG-207 and GBG-1 and testers IC-436638 and ABFBG-23RS were identified as good general combiners for days to 50% flowering, plant height, number of pods plant-1, pod length, number of seeds pod-1 and 100 seed weight. The crosses TBG-104×IC-436638, MBG-1070×LBG-20, TU-94-2×ABFBG-26RD and TU-94-2×LBG-20 have shown significantly favorable specific combining ability effects for seed yield plant-1 as well as yield attributes. Most of the crosses exhibiting high specific combining effects involved high×low combinations indicating additive×dominance, dominance×dominance type of gene interactions. Studies on heterosis indicated that majority of crosses showing high specific combining ability effects also exhibited high heterosis. The cross TBG-104×IC-436638 recorded high estimates of heterosis for seed yield plant-1 and also for number of clusters plant-1, pod length and biological yield plant-1. The superior crosses identified were TBG-104×IC-436638, TU-94-2×ABFBG-26RD and GBG-1×LBG-20 could be exploited for recombination breeding for development of varieties.